Acquired demyelinating disorders of central nervous system: A pediatric cohort - Gulati, Sheffali (Ann Indian Acad Neurol, 2015)
OBJECTIVE: This is a retrospective chart review of consecutive children with acquired demyelinating disorders presenting to a north Indian tertiary care hospital over 4 years. The aim of this review is to describe all the patients (with single event as well as those with recurrences) with detailed description of those who recurred. MATERIALS AND METHODS: Overall 35 cases were reviewed and their clinical presentations, diagnosis, management, and follow-up are being presented. RESULTS: Out of 35 cases, 24 did not show any recurrences (seven acute disseminated encephalomyelitis (ADEM) and 17 clinically isolated syndromes). Amongst the 11 patients with recurrent demyelination, majority were multiple sclerosis (8/11, 72.7%) followed by neuromyelitis optica (NMO; 2/11), and multiphasic ADEM (1/11). The median disease duration and follow-up since onset for those with recurrent episodes is 4 years (2.5-4.5 years). Steroids caused significant improvement in acute episodes of demyelination. However, recurrent demyelinating disorders like multiple sclerosis and NMO required long-term immunomodulation. Azathioprine currently is the most favored long-term immunomodulator used in NMO. Interferon-β and glatiramer acetate are currently recommended for multiple sclerosis. However, azathioprine may be a suitable alternative in a resource-limited setting. CONCLUSION: The consensus definitions for these groups of disorders need further validation in the pediatric age group. Studies with larger population size are required to characterize features that predict future recurrences.